Kecerdasan Adversitas, Motivasi Diri, dan Minat Berkarir di Bidang Perpajakan: Peran Pemahaman Tri-Nga - Fuadhillah Kirana Putri; Ananda Anggun Safara A. Rachmat; Suyanto Suyanto; Nur Anita Chandra Putry (Universitas Negeri Surabaya, 2023)
The low number of tax officers in Indonesia is a great opportunity for economics graduates to consider choosing a career in taxation. Economics scholars consider that a career in taxation is quite difficult. Therefore economics students are expected to have motivation and intelligence in facing challenges and difficulties. This study aims to test whether adversity intelligence and self-motivation have a positive effect on career interest in taxation. In addition, this study also aims to test whether understanding Tri-Nga can strengthen the effect of adversity intelligence and self-motivation on career interest in taxation. The research sample was 227 students of the Faculty of Economics at Tamansiswa Universities throughout Indonesia. Hypothesis testing was carried out using multiple linear regression and moderated regression analysis (MRA). The results of the study prove that adversity intelligence and self-motivation have a positive effect on career choices in the field of taxation and understanding Tri-Nga can strengthen the positive influence of adversity intelligence and self-motivation on career intentions in the field of taxation.